School-based instructional leadership support for information technology and computer applications technology subject teachers - Dokter, Sunia Marshell (University of the Free State, 2020)
The objective of this quantitative study was to determine who the instructional leaders are for information technology (IT) and computer applications technology (CAT) in schools, what activities characterise instructional leadership, what new competencies school-based leaders need to develop in order to be effective in their new roles as technology leaders, and how to improve instructional leadership support for IT and CAT subject teachers. The framework for this study combined three different perspectives: instructional leadership, distributed leadership and ideas on technological pedagogical content knowledge (TPACK). A pencil-and-paper questionnaire form was distributed to 50 CAT and IT teachers at the secondary schools that offer CAT or IT in the Free State province. Descriptive analysis was carried out using SPSS Version 20.0. The statistics used were descriptive statistics and inferential statistics. The findings of the study shed light on how schools provide instructional leadership support to IT and CAT teachers. From the findings it is clear that the absence of an instructional leader with technological background and knowledge might lead to CAT and IT teachers feeling neglected. Instructional leaders need to understand the nature and purpose of CAT/IT and to understand CAT/IT as part of the curriculum, and to clarify the responsibilities regarding technology leadership. It is recommended that further studies are undertaken to explore school technology leadership more broadly and in greater depth, to determine the explicit role of technology leadership for CAT and IT subject teachers.
Keywords: Dissertation (M.Ed. (School for Mathematics, Natural Sciences and Technology Education), 2020; Instructional leaders; Instructional leadership support; Distributed leadership; Technological pedagogical content knowledge (TPACK); Information technology (IT); Computer applications technology (CAT)